A continuous metal-insulator transition driven by spin correlations - Yejun Feng (Nature Portfolio, 2021)
The Mott transition is a celebrated example of a metal-insulator transition driven by electron correlations. Here, using magnetoresistance measurements, the authors demonstrate the presence of a spin-driven metal-insulator transition, where the insulating gap only opens below the Neel temperature.